2009
DOI: 10.1577/h08-012.1
|View full text |Cite
|
Sign up to set email alerts
|

Virulence Variation of White Spot Syndrome Virus in Pacific White Shrimp Litopenaeus vannamei

Abstract: The virulence of seven geographic isolates of white spot syndrome virus (WSSV; genus Whispovirus; China [strain CH1995], Nicaragua [strain N2000], Honduras [strain H2000], Ecuador [strains E-L1999 and E-LT2002], and Mexico [strains M-M2001 and M-LP2001]) was compared using a series of challenge experiments, each lasting 10 d. For each isolate, four quantified dilutions (10(-6), 10(7), 10(-8), and 10(-9)) of a viral inoculum were prepared from WSSV-infected shrimp tissue. Each viral inoculum was injected into 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 44 publications
1
14
0
2
Order By: Relevance
“…In other words, selection at the between-host level could – in an endemic situation – predominate over selection for faster replication at the within-host level (for examples of conflicting levels of selection see [27], [28]). Regional differences in WSSV virulence [29] and higher within-host competitive fitness of a WSSV variant with a small genome [8] are observations congruent with this hypothesis. Experimental quantification of transmission [30], [31] of geographical isolates under different conditions (e.g., host density, super-infection vs. co-infection) would provide a good test of this hypothesis.…”
Section: Discussionsupporting
confidence: 54%
“…In other words, selection at the between-host level could – in an endemic situation – predominate over selection for faster replication at the within-host level (for examples of conflicting levels of selection see [27], [28]). Regional differences in WSSV virulence [29] and higher within-host competitive fitness of a WSSV variant with a small genome [8] are observations congruent with this hypothesis. Experimental quantification of transmission [30], [31] of geographical isolates under different conditions (e.g., host density, super-infection vs. co-infection) would provide a good test of this hypothesis.…”
Section: Discussionsupporting
confidence: 54%
“…Más aún, el efecto de diferentes temperaturas en combinación con bajas y altas salinidades usado en criaderos comerciales, no ha sido bien analizado durante las etapas larvales de esta especie (2,6). Por tanto, es necesario prestar atención a las variaciones de estos factores abióticos durante el cultivo a gran escala (11), en aguas de baja salinidad por el prominente desarrollo de la camaronicultura tierra adentro (12,13), así como, en aguas con altas salinidades y temperaturas, donde su vulnerabilidad a enfermedades, ha provocado mortalidades y dificultades en la producción del camarón en todas las tallas y edades de distintos proveedores durante la estación calurosa o seca (15,16 …”
Section: Vannamei Is Commonly Known As the Whiteunclassified
“…Therefore, focusing on the variations of these abiotic in large scale breeding (11), in waters with low due to the development of onshore shrimp breeding (12,13), and in waters with high salinity and temperature, where they are vulnerable to disease, have both lead to mortality and difficulties in shrimp production over all sizes and ages bred by different suppliers during the warm or dry season (15,16).…”
Section: Materiales Y Métodosmentioning
confidence: 99%
“…Viral virulence depends on many factors, a number of which have been explored for WSSV. There is great variation in the virulence of different WSSV genotypes (Laramore, Scarpa, Laramore, & Lin, ; Marks, van Duijse, Zuidema, van Hulten, & Vlak, ; Pradeep, Karunasagar, & Karunasagar, ; Waikhom, John, George, & Jeyaseelan, ; Zwart, Dieu, Hemerik, & Vlak, ). Moreover, during its spread throughout farms in Asia, WSSV appears to have evolved a smaller genome and higher virulence (Dieu et al., ; Marks et al., ; Zwart et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have shown that the rate of WSSV infection depends on virus particle dose (Escobedo‐Bonilla et al., ; Laramore et al., ; Marks et al., ; Prior, Browdy, Shepard, Laramore, & Parnell, ). It has also been suggested that WSSV virus particles might be acting independently during the infection process because dose–response is similar to predictions of the independent action hypothesis (IAH) model (Dieu, Zwart, & Vlak, ).…”
Section: Introductionmentioning
confidence: 99%